Diffusive behavior of a surface layer in BaTiO3 crystals grown by Remeika method. Issue 3 (24th November 2014) - Dul'kin, Evgeniy; Roth, Michael
Abstract : BaTiO3 crystals, grown by Remeika method, were studied by means of acoustic emission and dielectric response. It is established, that the phase transition in the surface layer occurs on 13 °C below in comparing with the crystals bulk. It is observed, that the imaginary dielectric response of a crystal surface layer exhibits an essential smearing and slight frequency shift to higher temperatures. Reasons of such properties are discussed from a viewpoint of diffusive phase transition, taking place in the surface layer, enriched by K + ions from KF flux.